Design and Study of Clothing Structure for People with Limb Disabilities (Journal of Fiber Bioengineering and Informatics, 2018)
The human body's features are the key to design clothing structure. Between people with physical disabilities and normal people, there are evident differences in their living requirements. Embellishment is needed because of physical distortion; as well as, functionalized design is strongly required to allow more independence in dressing and more self sufficiency in daily activities. Therefore, pattern design should encourage the health recovery, improve living style, and realize personal expectations. The final aim is to allow people with a disability a life of self-respect and facility, and enable them to mingle with family and society to a greater extent. In the past, there had been some clothing designed for people with disabilities. However most of those designs lack aesthetic consideration, and usually focus on the excessively direct aspect of function. Based on the characteristics of human body and movements, particularity for people with limb disabilities, the clothing pattern was analysed by means of real examples. Combining the knowledge of human engineering (ergonomics), textile materials and apparel technology, special modifications were designed in the garment to de-emphasize visual evidence of a person's disability, and strengthen function and convenience to meet the needs of body activities. Clothing designed for disabled people should contain elements of both function and beauty, which can help them rise to the &#8220convenient&#8221, &#8220beautiful&#8221 and &#8220functional&#8221 level from the &#8220inconvenient&#8221, &#8220concealment&#8221 level. As a result, improvement in the quality of life of people with limb disabilities will be achieved.
Keywords: clothing structure; people with limb disabilities; functionalized design; body features; way of motion; embellishment of the body